2004
DOI: 10.1080/14622200410001676422
|View full text |Cite
|
Sign up to set email alerts
|

Smoking behavior among hospital staff still influences attitudes and counseling on smoking

Abstract: Smoking among health professionals has been shown to influence smoking-related knowledge and counseling in clinical practice. The evidence regarding smoking as a risk factor has increased in the past decade. The present study was carried out in 2000 and investigated the associations between individual smoking behavior among hospital staff and (a). smoking-related knowledge, (b). attitudes toward counseling on smoking, and (c). self-reported smoking-related counseling provided by the staff. The study was based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 19 publications
3
37
0
3
Order By: Relevance
“…8,49,50 Had the nonforensic staff in the present study been better able to prevent access to tobacco, the results there might have mirrored those in maximum security. Indeed, redoubled efforts at the end of the second year to eliminate tobacco might have been partly responsible for the return of aggression to pre-ban levels.…”
Section: Implications For Behavioral Healthmentioning
confidence: 45%
“…8,49,50 Had the nonforensic staff in the present study been better able to prevent access to tobacco, the results there might have mirrored those in maximum security. Indeed, redoubled efforts at the end of the second year to eliminate tobacco might have been partly responsible for the return of aggression to pre-ban levels.…”
Section: Implications For Behavioral Healthmentioning
confidence: 45%
“…Even though 70% of cancer patients who smoke are motivated to quit smoking, only 56% of physicians recommend that their cancer patients who smoke stop smoking 52 and most oncology providers do not provide smoking interventions beyond advice to quit. 53 Our work 54 and the work of others [55][56][57][58][59] have shown that the major barriers to providers implementing smoking cessation services included lack of expertise and time. Education programs for health care providers as well as dedicated smoking cessation programs would improve tobacco treatment for cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Al respecto, cabe mencionar que abordar el tabaquismo en los funcionarios de la salud trasciende más allá de ellos mismos, ya que ellos ejercen gran infl uencia sobre el tabaquismo general: desalientan el consumo, sirven como ejemplo, fomentan el ejercicio de la ley sobre la prohibición de fumar en los establecimientos de salud y sensibilizan a la sociedad sobre el tabaquismo como FR. De hecho, está demostrado que los médicos que no fuman, están más interesados en desalentar el consumo en sus pacientes fumadores 16,17 . Investigaciones en el área de la promoción de la salud en el ambiente laboral han documentado efectividad no sólo en cese tabáquico, sino además en antropometría, hábitos alimenticios, actividad física y morbimortalidad general 18 .…”
Section: Discussionunclassified